PENGUKURAN REKAHAN, PADA BATUAN SEDIMEN DI SUNGAI CIPOGO PADALARANG KABUPATEN BANDUNG JAWA BARAT - Rafiqah Indah Sari; Rexy Elnando; Nurfajri Indra; Gina Rahayu; Sildila Sari; Mufti Khairatunnisa; Ronal Wilnika; Devi L Maria; Reza Nofri Andika; Muhammad Noval; Dian Adhetya Arif (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
Rock is a solid substance that contains minerals and is formed naturally. Joint is a fractured plane without a shift in the rock body and can be present systematically formed by tectonic forces and can be analyzed as an interpretation of its forming tectonic forces from systematic data. This research was conducted in Sugai Cibogo, Padalarang, West Bandung Regency, with coordinates 06049'29.07